1977
DOI: 10.1002/bjs.1800640515
|View full text |Cite
|
Sign up to set email alerts
|

The implications of scrotal interference for the preservation of spermatogenesis in the management of testicular tumours

Abstract: Seminal analyses have been performed in 14 patients who have received radiation therapy following unilateral orchidectomy for testicular tumours. In patients receiving scrotal in addition to para-aortic and pelvic lymph node irradiation azoospermia occurred in 17 out 18 specimens examined, whereas in those patients not requiring scrotal irradiation, restoration of spermatogenesis occurred. The difference is a result of the increased dose of radiation received by the remaining testicle when the contralateral si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Thus the mortality due to second tumour is approximately 1 % and considerably less than this for patients whose second tumours were Stage 1. There is thus no justification for treatment policies which electively treat the remaining testis, since the probability of a second tumour is low, the probability of cure of the second tumour if it arises is good, and the chance of the patient remaining fertile following nodal irradiation is good provided high cord ligation has been performed in the appropriate manner (Thomas et a/. , 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the mortality due to second tumour is approximately 1 % and considerably less than this for patients whose second tumours were Stage 1. There is thus no justification for treatment policies which electively treat the remaining testis, since the probability of a second tumour is low, the probability of cure of the second tumour if it arises is good, and the chance of the patient remaining fertile following nodal irradiation is good provided high cord ligation has been performed in the appropriate manner (Thomas et a/. , 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Although the immediate and longterm morbidity of the relatively modest radiation dose employed is low, there may be an increased risk of peptic ulceration (Hamilton et al, 1986) and non-testicular malignancy (Hay et al, 1984). Furthermore, the scattered radiation dose to the contralateral testis can result in temporary or permanent failure of spermatogenesis, particularly if the inguinal nodes and scrota1 sac are irradiated (Thomas et al, 1977).…”
mentioning
confidence: 99%
“…In general, semen analyses in groups of 7 to 86 selected patients with unilateral testicular cancer have shown that most of the patients had impaired semen quality before radio-and chemotherapy (Sandeman 1966;Haubrich & Harms 1973; Thomas et al 1977;Bracken & Smith 1980;Kuber et al 1980;FossP et al 1982;…”
mentioning
confidence: 99%
“…Results obtained from groups of 8 to 25 selected patients with unilateral testicular cancer suggest, that this dose of scattered radiation induces temporary azoospermia in some patients. There is then a return to the pre-treatment sperm count within 1 to 2 years in a few patients, while a longer period for restoration is needed in the majority of patients (Sandeman 1966; Thomas et al 1977;Kuber et al 1980;Thachil et al 1981;Greiner 1982;Hahnetal. 1982).…”
mentioning
confidence: 99%